Comparison of graphic expression of dependences of transporter cut profile of threshing-separating unit on the second volume and spike fraction humidity - A. G. Dyachenko; T. P. Savostina; S. B. Imad (Advanced Engineering Research, 2019)
Introduction. Threshing is a multifactorial process which is affected, in particular, by the feedrate of the crop, the specific weight of the threshed grain and return, separation rates, weediness and moisture of the crop. From this point of view, the issues of optimizing the profile of the transporter cut, which allows for threshing and separation with the least effort, are also relevant. It was also experimentally established that the threshing process is affected by the volume of grain material delivered per second (second feed) and the unit velocity.Materials and Methods. The studies were conducted on a test bench equipped with a threshing-separating device in the form of a single-cavity hyperboloid. When performing the work, the width of the drum was divided into three zones, and the length – into five cells. Wheat grain, obtained through threshing and separation in each zone and cell, came to individual containers. Straw was collected separately. Then, the grain and straw were weighed. The resulting data was processed by statistical and mathematical methods.Research Results. The lengths of each cell were calculated based on the ratio of the total separation and the amount of grain mass per unit length. The lengths of each cell were calculated depending on changes in humidity. Indicators of the ratio between mass humidity and cell length are presented in the form of a table. By the given table values for different moisture levels of the grain mass, graphs were constructed, each of which was described by a mathematical model considering the drum length and width. An averaged cut profile is presented for the treated plant mass with humidity of 8%, 12%, 16%, 20%, and 24%.Discussion and Conclusions. Analysis of the data in this paper and earlier ones provides the comparison of the graphic expression of the dependences of the transporter cut profile on the second volume and humidity of the grain mass entering it. It has been established that the cut profile curves are identical along the entire length of the drum. The confidence factor is close to 1, which indicates the accuracy of the model. The identity of the averaged cut profiles is obviously dependent on moisture of the plant mass and on the second feed.